Marketing to the Social Web: How Digital Customer Communities Build Your Business - Larry Weber (Wiley, 2009)
An updated and expanded Second Edition of the popular guide to social media for the business community Marketers must look to the Web for new ways of finding customers and communicating with them, rather than at them. From Facebook and YouTube to blogs and Twitter-ing, social media on the Internet is the most promising new way to reach customers. Marketing to the Social Web, Second Edition helps marketers and their companies understand how to engage customers, build customer communities, and maximize profits in a time of marketing confusion. Author and social media guru Larry Weber describes newly available tools and platforms, and shows you how to apply them to see immediate results and growth.
Keywords: Business